1999
DOI: 10.1046/j.1365-201x.1999.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in skeletal muscle fibre damage after eccentrically biased downhill running in rats

Abstract: Specific antibodies against structural proteins of muscle fibres (actin, desmin, dystrophin) and extracellular matrix (fibronectin) were used to study the effect of eccentrically biased downhill running exercise (13,5 degrees, 17 m min(-1), 130 min) on the magnitude and properties of myofibre injury in the quadriceps femoris muscle of male and female rats. Muscle beta-glucuronidase activity, a quantitative indicator of muscle damage, showed clearly smaller increase in female than in male rats during the 4-day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 23 publications
6
76
2
Order By: Relevance
“…There were no consistent gender differences noted in any of the results. These results are in contrast to the reported effectiveness of estrogen supplementation in attenuating indices of neutrophil infiltration following running exercise in male and ovariectomized female rats (Tiidus and Bombardier, 1999;Tiidus et al, 2001), and in the reported attenuation of indices of muscle damage and bGLU activity following downhill running in male versus female rats (Komulainen et al, 1999). The results also contrast most (i.e., Node et al, 1997;Squadrito et al, 1997;Zhai et al, 2000) but not all studies (Grist et al, 2002), which suggest a reduction on indices of neutrophil infiltration and damage with estrogen supplementation following ischemia in cardiac muscle.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…There were no consistent gender differences noted in any of the results. These results are in contrast to the reported effectiveness of estrogen supplementation in attenuating indices of neutrophil infiltration following running exercise in male and ovariectomized female rats (Tiidus and Bombardier, 1999;Tiidus et al, 2001), and in the reported attenuation of indices of muscle damage and bGLU activity following downhill running in male versus female rats (Komulainen et al, 1999). The results also contrast most (i.e., Node et al, 1997;Squadrito et al, 1997;Zhai et al, 2000) but not all studies (Grist et al, 2002), which suggest a reduction on indices of neutrophil infiltration and damage with estrogen supplementation following ischemia in cardiac muscle.…”
Section: Discussioncontrasting
confidence: 55%
“…Komulainen and colleagues (1999) and Amelink and colleagues (1991) have reported female rats as having attenuated indicators of muscle damage following running exercise when compared to male rats. These differences have been attributed to the potential influence of estrogen (Komulainen et al, 1999). However, gender differences in muscle damage indicators have not been demonstrated consistently following exercise in humans (i.e., Stupka et al, 2000;Clarkson and Sayers, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of estrogen seen in ovariectomized mice leads to progressive muscle atrophy (45). Estrogens may help stabilize membranes (115), act as antioxidants (102,103), and thereby protect from muscle damage and inflammation (47,108). However, others have shown estrogens to be negative regulators of muscle mass.…”
Section: Integration Of Signaling Pathways To Modulate Ups Function Imentioning
confidence: 99%
“…Several studies examined the susceptibility for eccentric exercise between males and females in rats (22,23) and humans (4,(24)(25)(26). Downhill running caused larger increases in serum levels of skeletal muscle proteins and enzymes in males than in females, probably due to an involvement of a larger muscle mass in males (10).…”
Section: Introductionmentioning
confidence: 99%